Pengaruh Kekompakan Perkotaan Terhadap Tingkat Emisi dari Sektor Energi Kegiatan Transportasi - Alim Giasi; Ananto Yudono; Arifuddin Akil (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2017)
Marisa is the sub-district with the highest population growth rate in Pohuwato district, this has resulted in urban sprawl symptoms that have an impact on the length of travel needed. The increase in the length of the trip also has an impact on increasing its energy consumption. This study aims to identify the level of compactness of each kelurahan, calculate emission levels in each kelurahan and do correlation modeling to examine the effect of Marisa Urban compactness on emission levels. Based on the results of the study, urban Marisa is divided into 2 groups of space compactness namely, medium and low. There are two villages with moderate cohesiveness and four villages with low cohesiveness. Emission levels produced in urban Marisa range from 32 to 87 Kg Co2. Different levels of urban compactness affect different levels of emissions. The result of modeling with correlation shows that the compactness index variable correlates significantly not in the direction of greenhouse gas emissions, which means, if Marisa's compactness index increases, there will be a decrease in house gas emissions. It can be seen that the results of the analysis have one asterisk which means that the compactness and greenhouse gas emissions variable correlates significantly at the 0.05 or 95% level.